Tanshinone IIA protects rabbits against LPS-induced disseminated intravascular coagulation (DIC) - Wu Liang-cai; Lin Xi; Sun Hao (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the effects of tanshinone IIA (Tan IIA), a lipophilic diterpene from the Chinese herb Salvia miltiorrhiza, on lipopolysaccharide (LPS)-induced disseminated intravascular coagulation (DIC) in rabbits. Methods: LPS-induced DIC model was made in adult male New Zealand rabbits by continuous intravenous infusion of LPS (0.5 mg/kg) via marginal ear vein for 6 h. The animals were simultaneously administered with Tan IIA (1, 3 and 10 mg/kg) or heparin (500 000 IU/kg) through continuous infusion via the contralateral marginal ear vein for 6 h. Before and 2 and 6 h after the start of LPS infusion, blood samples were taken for biochemical analyses. Results: Continuous infusion of LPS into the rabbits gradually impaired the hemostatic parameters, damaged renal and liver functions, increased the plasma TNF-α level, and led to a high mortality rate (80%). Treatment of the rabbits with Tan IIA dose-dependently attenuated the increase in activated partial thromboplastin time (APTT), prothrombin time (PT) and fibrin-fibrinogen degradation products (FDP); ameliorated the decrease in plasma levels of fibrinogen and platelets; and reversed the decline in activity of protein C and antithrombin III. Meanwhile, the treatment significantly suppressed the increase in the plasma levels of aminotransferase, creatinine and TNF-α, and led to much lower mortality (46.7% and 26.7% for the medium- and high-dose groups). Treatment of the rabbits with the high dose of heparin also effectively improved the hemostatic parameters, ameliorated liver and renal injuries, and reduced the plasma level of TNF-α, and significantly reduced the mortality (33.3%). Conclusion: Tan IIA exerts a protective effect against DIC in rabbits.